Research review of digital modeling technologies with 3D spatial visualization for pipelines - Xin LIU; Shengwen TU; Yanfang HOU; Dong LIN; Jie SHU; Yu TANG (You-qi chuyun)
ObjectiveDigital modeling technologies with three-dimensional (3D) spatial visualization have emerged as a crucial approach in the pipeline sector, particularly for emergency repairs and operation and maintenance management, leveraging their abilities to accurately represent the 3D spatial layout of underground pipelines and offer clear visual display. As visualization theories and technological practices continue to evolve, selecting appropriate visual modeling technologies adaptable to on-site requirements is essential for enhancing emergency response capabilities and improving the efficiency of routine pipeline management. MethodsFrom the perspective of software and algorithm characteristics, this paper classifies visual modeling technologies for pipelines into three categories: 3D modeling software, secondary development based on existing components, and underlying development. The principles, characteristics, and application scenarios of each category are described, with a comparative analysis of their advantages and disadvantages. Given the deficiencies in these technologies, particularly when addressing adverse geological areas frequently encountered by oil and gas pipelines, such as challenges in clearly representing pipeline deformation and subsequent difficulties in manual operation and maintenance, this paper discusses the applications and benefits of new technologies in pipeline visualization, including Inertial Measurement Unit (IMU), Light Detection and Ranging (LiDAR), Augmented Reality (AR), Digital Twin (DT), and the Internet of Things (IoT). Furthermore, from the perspectives of data collection, feature information architecture, and multi-system integration, this paper analyzes the challenges faced by the development of digital modeling technologies with 3D spatial visualization for pipelines and outlines prospects for future development trends in this field. ResultsVisual modeling technologies for pipelines facilitate the establishment of 3D visualization systems through rapid modeling based on element information databases, encompassing pipelines, appendages, defects, and service scenarios. These visualization systems accurately reflect the spatial relationships of pipelines, providing effective guidance for selecting and planning pipeline routes, as well as for excavation during maintenance and rush repair. Additionally, the integration of new technologies has led to significant advancements in the visual modeling of pipelines, particularly in improving the accuracy of detection data, representing trends in pipeline deformation, enhancing system interactivity, and enabling real-time monitoring of pipeline data. These developments have resulted in more comprehensive functionalities for visualization systems and improved operational and maintenance efficiency. ConclusionGiven the current emphasis on multi-technology integration in digital modeling with 3D spatial visualization for pipelines, developers should select appropriate methods based on specific requirements to ensure the applicability of their systems. Future efforts should focus on several key areas, including high-precision data acquisition, multi-source data fusion, optimization of real-time performance for visualization systems, and the promotion of intelligent and automated applications, aiming to achieve comprehensive visual interaction that encompasses pipeline spatial positions, defect information, and operational condition data, ultimately enhancing the intrinsic safety of pipelines.